Ab initio study of metalosalen complexes binding to DNA - Jahangiri Lahkani Marjane; Ghassemi Ghassem; Sohrabi Nasrin; Rasooli Nahid (Видавництво Львівської політехніки, 2011)
Geometry optimizations of metal complexes of Salen(bis(Salicylidene)1,2-ethylenediamine) were carried out at HF(Hartree-Fock) and DFT(Density Functional Theory) methods employing Lanl2DZ basis set. In this work structural,energies, bond lengths and other physical properties between Mn2+,Cu2+ and Ni2+ ions coordinated by salen–type ligands are examined. All calculations were performed using Gaussian 98W program series. To investigate local aromaticities, NICS(Nucleous Independent Chemical Shift) were calculated at all centers of rings. The higher the band gap indicating a higher global aromaticity. The possible binding energies have been evaluated. We have evaluated Frequencies and Zeropoint energy with freq calculation. The NICS Results show Ni(II) complexes are antiaromatic and aromaticites of Mn(II) complexes are larger than Cu(II) complexes. The energy Results show Cu(II) complexes are stability than Mn(II) and Ni(II) complexes.
Keywords: density functional theory(DFT); frequency calculation; hartree-fock(HF); nucleous independent chemical shift(NICS); salen(bis(salicylidene)1,2-ethylenediamine)